THE ROLE OF MANAGEMENT IN PROMOTING A MOTIVATIONAL WORK SETTING FOR NURSES - Karien Jooste; Oscar Kilpert (AOSIS, 2002)
The use of motivation and reward strategies is necessary for empowerment of staff members in their work situation. For motivation to occur in a health service, strategies should focus on self-motivation, expansion and enrichment of tasks, acknowledgement of work performances of nurses, rewards for outstanding service and constructive feedback by managers to nurses. A descriptive, explorative study was done to investigate the current motivational strategies used in health services management settings. A sample of 112 nurses completed a questionnaire that provided information relating to the employer/health service (organisational culture, personal values and expectations), the direct supervisor of a staff member (working relationships, interpersonal skills of the supervisor) and self-concept. Important strategies that should be employed by managers in the establishment of a motivational environment for staff are integrated into a conceptual framework.